Design and rationale of a prospective, multi‐institutional registry for patients with sinonasal malignancy. (10th June 2016) - Beswick, Daniel M.; Holsinger, F. Christopher; Kaplan, Michael J.; Fischbein, Nancy J.; Hara, Wendy; Colevas, A. Dimitrios; Le, Quynh‐Thu; Berry, Gerald J.; Hwang, Peter H.
Abstract : Objectives/Hypothesis: Assessment of patients with sinonasal malignancy is challenging due to the low disease incidence and diverse histopathology. The current literature is composed mainly of retrospective studies with heterogeneous cohorts, and the rarity of cases limits our understanding of disease characteristics and treatment outcomes. We describe the development of a prospective, multi‐institutional registry that utilizes cloud‐based computing to evaluate treatment outcomes in patients with sinonasal cancer. Methods: A web‐based, secure database was built to prospectively capture longitudinal outcomes and quality‐of‐life (QoL) data in patients diagnosed with sinonasal malignancy. Demographics, tumor staging, and treatment outcomes data are being collected. The Sinonasal Outcome Test‐22 and University of Washington Quality of Life Questionnaire are administered at presentation and at recurring intervals. To date, seven institutions are participating nationally. Conclusion: This prospective, multi‐institutional registry will provide novel oncological and QoL outcomes on patients with sinonasal malignancy to inform management decisions and disease prognostication. The application of cloud‐based computing facilitates secure multi‐institutional collaboration and may serve as a model for future registry development for the study of rare diseases in otolaryngology. Level of Evidence: 2C Laryngoscope, 126:1977–1980, 2016